A review of additive manufacturing technology and cost estimation techniques for the defence sector - Busachi, Alessandro; Erkoyuncu, John Ahmet; Colegrove, Paul A.; Martina, Filomeno; Watts, Chris; Drake, Richard (Elsevier, 2017)
“Additive Manufacturing” (AM) is a promising technology which will provide major advantages to Defence Support Service providers, given its ability of delocalised manufacturing near the point of use. The technology is gaining increasing interest due to its disruptive potential. AM groups together a wide range of different approaches which have the ability to convert a 3D file into a physical product by depositing layer upon layer of material. AM is still under development and considered an immature technology. This immaturity provides high level of uncertainty around key indicators such as time and cost. These indicators represent also key decision variables to evaluate AM and compare it with traditional manufacturing. This review paper represents an investigation of existing knowledge on AM and aims to present to the reader the various AM approaches with a detailed focus on the most applicable technologies to Defence Support Services. The paper is structured as follows, firstly the various technologies of AM and their economic aspects are presented, secondly the cost modelling techniques are investigated and finally a discussion is carried out. The contribution of this paper is to present to Defence Support Service stakeholders the various AM technologies and cost modelling techniques for measuring the product or service cost.
Keywords: Technology Acquisition; Cost Estimation; Activity Based Costing; Additive Manufacturing; Defence Support Services